2017
DOI: 10.1590/1518-8345.1751.2935
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with acquisition of carbapenem-resistant Enterobacteriaceae

Abstract: Objective:to identify possible risk factors for acquisition of Enterobacterial strains with a marker for resistance to carbapenems. Methods:exploratory case-control study performed in hospital settings. The study sample consisted of patients with biological specimens that tested positive for carbapenem-resistant Enterobacteriaceae (cases), with the disk diffusion test and Etest, and controls with biological samples testing negative for carbapenem-resistant Enterobacteriaceae. In all, 65 patients were included:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
3
0
5
Order By: Relevance
“…In the current study, comparison between the different hospital departments regarding the isolation of MBL producing strains showed there was no statistically significant difference between the strains (p>0.05). Similar results reported by Lavagnoli et al who observed no association between the acquisition of carbapenemaseproducing Enterobacteriaceae (CPE) and the admission at different hospital departments in a Brazilian study [29]. However, Masaeli and associates, who collected 423 clinical isolates reported that admission to the ICU was a major risk factor for the acquisition of MBL by using univariate analysis [30].…”
Section: Discussionsupporting
confidence: 72%
“…In the current study, comparison between the different hospital departments regarding the isolation of MBL producing strains showed there was no statistically significant difference between the strains (p>0.05). Similar results reported by Lavagnoli et al who observed no association between the acquisition of carbapenemaseproducing Enterobacteriaceae (CPE) and the admission at different hospital departments in a Brazilian study [29]. However, Masaeli and associates, who collected 423 clinical isolates reported that admission to the ICU was a major risk factor for the acquisition of MBL by using univariate analysis [30].…”
Section: Discussionsupporting
confidence: 72%
“…No tocante a enterobactérias, verificou-se valores < 1 × 10 2 UFC/mL para todas as formulações de fermentados. As enterobactérias são micro-organismos gram negativos, encontrados na natureza, que têm a capacidade de colonizar o trato gastrointestinal de seres humanos e animais, e dentre essa família encontram-se diversos gêneros, como: Klebsiella, Enterobacter, Escherichia, Serratia, Citrobacter, Salmonella, Proteus e Morganella (Seibert et al, 2014;Lavagnoli et al, 2017), sendo a maioria capaz de causar problemas de saúde ao ser humano se consumidos em quantidades excessivas e/ou se forem consumidas as suas toxinas.…”
Section: Caracterização Microbiológica Dos Fermentados Alcoólicos De Mangabaunclassified
“…Conclusion: Prognostic factors of patients with Klebsiella pneumoniae producing carbapenemase were: PELOD-2 score on the day of infection, 48 hours after infection and on the day of death or hospital discharge; use of parenteral nutrition (PN) seemed to be a protective factor for death. intestinal de animais e seres humanos [9][10] . Sua relevância no ambiente hospitalar está relacionada às infecções da corrente sanguínea, trato urinário, infecções de sítio cirúrgico e pneumonias [9][10] .…”
Section: Cdcmentioning
confidence: 99%
“…intestinal de animais e seres humanos [9][10] . Sua relevância no ambiente hospitalar está relacionada às infecções da corrente sanguínea, trato urinário, infecções de sítio cirúrgico e pneumonias [9][10] .…”
Section: Cdcunclassified
See 1 more Smart Citation